Efficacy and Safety of Individualized Coaching After Stroke: the LAST Study (Life After Stroke). Issue 2 (February 2018) - Askim, Torunn; Langhammer, Birgitta; Ihle-Hansen, Hege; Gunnes, Mari; Lydersen, Stian; Indredavik, Bent; Engstad, Torgeir; Magnussen, Jon; Hansen, Anne; Schjørlien, Rune; Engen, Stian; Osmundnes, Randi Moxnes; et al.
Abstract : Background and Purpose—: The evidence for interventions to prevent functional decline in the long term after stroke is lacking. The aim of this trial was to evaluate the efficacy and safety of an 18-month follow-up program of individualized regular coaching on physical activity and exercise. Methods—: This was a multicentre, pragmatic, single-blinded, randomized controlled trial. Adults (age ≥18 years) with first-ever or recurrent stroke, community dwelling, with modified Rankin Scale <5, and no serious comorbidities were included 10 to 16 weeks poststroke. The intervention group received individualized regular coaching on physical activity and exercise every month for 18 consecutive months. The control group received standard care. Primary outcome was the Motor Assessment Scale at end of intervention (18-month follow-up). Secondary measures were Barthel index, modified Rankin Scale, item 14 from Berg Balance Scale, Timed Up and Go test, gait speed, 6-minute walk test, and Stroke Impact Scale. Other outcomes were adverse events and compliance to the intervention assessed by training diaries and the International Physical Activity Questionnaire. Results—: Three hundred and eighty consenting participants were randomly assigned to individualized coaching (n=186) or standard care (n=194). The mean estimated difference on Motor Assessment Scale in favor of control group was −0.70 points (95% confidence interval, −2.80, 1.39), P =0.512. There were no differences between the groups on Barthel index, modified Rankin Scale, or Berg Balance Scale. The frequency of adverse events was low in both groups. Results from International Physical Activity Questionnaire and training diaries showed increased activity levels but low intensity of the exercise in the intervention group. Conclusions—: The regular individualized coaching did not improve maintenance of motor function or the secondary outcomes compared with standard care. The intervention should be regarded as safe. Despite the neutral results, the health costs related to the intervention should be investigated. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01467206. Abstract : Supplemental Digital Content is available in the text.